(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Field trials were conducted during the 2021 and 2022 wet seasons at the research farm of the Institute for Agricultural Research, Samaru, Zaria to determine the best weed control treatment and fertilization rates on growth and bulb yield of onion (Allium cepa L.). The treatments were laid out in a Randomized Complete Block Design (RCBD) in split block arrangement and replicated three times. Weed species with higher Important Value Index was Cyperus rotundus in both seasons. Application of pendimethalin at 1.63 kg a.i ha-1 + one hoe weeding at 6 WAT and hoe weeding at 3 and 6 WAT recorded higher weed control index. A slight crop injury was recorded by application of pendimetalin + oxyfluorfen at 1.3 + 1.2 kg a.i ha-1. All weed control treated plots recorded higher growth parameters and bulb yield than the weedy check. In contrast, application of N.P.K + AZ at 65: 45: 45 kg ha-1 + 0 L ha-1, 0 kg ha-1 + 12 L ha-1 and the untreated control recorded higher weed control index. Application of N.P.K + AZ at 32.5: 22.5: 22.5 kg ha-1 + 6 L ha-1 and 65: 45: 45 kg ha-1 + 0 L ha-1 increased growth and bulb yield than other fertilization rates. In conclusion, all herbicides treatments were safe on onion and comparable to hoe weeding at 3 and 6 WAT in enhancing weed control index, growth performance and higher bulb yield. Application of N.P.K + AZ at 32.5: 22.5: 22.5 kg ha-1 + 6 L ha-1 and 65: 45: 45 kg ha-1 + 0 L ha-1 significantly (P ≤ 0.05) enhanced better growth and higher bulb yield than other fertilization rates in both seasons.